Accelerated peripheral nerve repair using surface-modified biomaterials for targeted capture of glial-derived growth factors post-neurorrhaphy. - Shiu-Jau Chen; Chih-Ming Lin; Chiung-Hui Liu; Yin-Hsiu Chen; Yu-Lin Hsieh; You-Cheng Lin; Yin-Hung Chu; Chung-Yao Ku; Wei-Li Liao; Wen-Chieh Liao (PLoS ONE)
Peripheral nerve injury (PNI) commonly leads to motor or sensory dysfunction, with nerve grafts being the standard treatment for neurorrhaphy. Despite advancements in biomaterials for nerve-tissue engineering, the rate of nerve regeneration remains slow. Therefore, this study aims to improve further the understanding of the impact of syndecan-3 (SDC3)-modified small intestine submucosa (SIS) on nerve reconstruction by employing two advanced approaches: cation recruitment and local growth factor delivery. Immunofluorescence staining confirmed the presence of SDC3 conjugated on the SIS. The enzyme-linked immunosorbent assay measured sustained glial cell line-derived neurotrophic factor (GDNF) levels in the SDC3-coated SIS. In vitro studies showed that SDC3-coated SIS retained GDNF in a dose-dependent manner, significantly enhancing Schwann cell proliferation compared with basal conditions. RSC96 cells proliferated most effectively on SDC3-coated SIS loaded with GDNF, and neuro-2A neurites were significantly longer on this material at 48 hours. One-month post-neurorrhaphy, morphological analysis revealed a 1.6 ±  0.02-fold increase in the number of β3-tubulin-positive axons in the GDNF+SDC3-coated SIS group compared to the SIS group. CMAP amplitude increases in the GDNF+SDC3-coated SIS group as more functioning motor axons are connected to the target muscle of ESN rats. This study provides valuable insights into the development of customized SDC3-coated SIS for promoting nerve tissue regeneration and accelerating rehabilitation.